Pelatihan Pemanfaatan Kecerdasan Buatan (Artificial Intelegence/AI) Sebagai Alat Bantu Pembelajaran Bagi Siswa/Wi SMA Negeri 1 Peusangan Siblah Krueng Kabupaten Bireuen: Pengabdian - Dani Pratama Putra; Akmal Izwar; Reza Fahmi; Rossy Azhar; Fina Meilinar; Erlia Hanum; Al Mizan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The rapid development of Artificial Intelligence (AI) technology presents both opportunities and challenges in the educational sector, particularly for high school students who often lack a comprehensive understanding of its potential as a learning tool. This community service activity aimed to enhance the digital literacy and AI utilization skills of students at SMA Negeri 1 Peusangan Siblah Krueng, Bireuen Regency. Using a quasi-experimental method with a one-group pretest-posttest design, the activity involved 50 eleventh-grade students selected through purposive sampling. The intervention consisted of interactive counseling on AI concepts and hands-on training using various AI applications like ChatGPT, Gemini, and Canva AI. Data were collected through questionnaires, observations, and documentation. The results showed a significant increase in students' understanding of AI concepts, ability to formulate effective prompts, and skills in operating AI applications independently. The average post-test scores across all assessed aspects, such as basic understanding, prompt engineering, and practical skills, increased substantially compared to pre-test scores. Students also demonstrated high enthusiasm and a positive attitude toward using AI in learning. This training successfully equipped students with the knowledge and skills to utilize AI as an effective, responsible, and productive learning aid, supporting their readiness for educational transformation in the digital era. Keywords: Artificial Intelligence, Learning Tool, Digital Literacy, Quasi-Experiment, High School Students